Safety Analysis of Advanced CANDU Reactor-700 (ACR-700) during Transient and Emergency Condition using ACR Simulator - Fathoni Shidik, Muhammad; Siti Nuraini Mahmudah, Rida (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2021)
The development of nuclear technology leads to improvement in nuclear power plant design. The latest generation of the nuclear reactor tries to rely more on passive system to minimize the human intervention and increase the safety of the nuclear power plant itself. ACR-700 is designed to be able to cope with some transients condition. This study try to simulate the condition of ACR-700 during the transient condition loss of one of reactor coolant pump using ACR Simulator developed by IAEA. The ACR-700 safety system successfully identify the malfunction and stop the malfunction to escalate. In addition to that, this paper also try to simulate the previous transient condition with another malfunction in reactor setback and setback system, one of the safety system of the ACR-700.